Association of Screen Time with Shoulder Pain and Disability among Office Workers of Rawalpindi and Islamabad: A Cross-Sectional Analytical Study - Sidra Hanif, Urooj Fatima, Kiran Afzal, Hafsah Gul Khattak, Mehjabeen Farooqui, Muhammad Mustafa (Pakistan Journal of Medical & Health Sciences, 2022)
Purpose: The study was conducted to determine the association of screen time with the shoulder pain and disability among office workers. Method: A cross sectional Analytical study was conducted on office workers in Islamabad and Rawalpindi from July 2020 To January 2021. 370 office workers of age 25-45 and having working hours greater than 6 were included in the study. Association between the variables was checked by calculating r value of SPADI variables individually with screen time and it was 0.271 for Screen time and SPADI pain scale, 0.240 for Screen time and SPADI disability scale, and 0.245 for Screen time and total SPADI score. Findings: As all the values lies between 0-0.3, it shows that there is a weak positive co-relation between the Screen time and Shoulder pain and disability. The results of the current study concluded that there is a week positive correlation between the screen time and SPADI. Practical Implications: Overusing screen-based technologies is creating issues in the community by harming physical health, contributing to bad posture, and misaligning the skeleton. Therefore, the research will provide a starting point for data from which additional research can be done. Keywords: SPADI pain and disability, Shoulder disability, Painful Shoulder, Office workers and screen time.